Predicting struvite formation for phosphorus recovery from human urine using an equilibrium model - Harada, H (Water science and technology : a journal of the International Association on Water Pollution Research, 2006)
Interest in phosphorus recovery from urine diverted from faeces has been growing recently. Phosphorus in urine can be precipitated out as struvite (MgNH4PO4 x 6H2O) with addition of magnesium salt under alkaline conditions. Struvite formation, however, should be more well understood for its practical application. We predicted the struvite formation with a development of a new equilibrium model. The model considered the formation of eight different kinds of precipitates, including struvite, with effects of ionic strength and temperature. In addition, experiments on struvite formation in urine were conducted for the model validation. The model prediction of struvite formation had good agreement with the experimental results. The optimum pH to form struvite was predicted to be 9.4-9.7. In order to precipitate 99% of phosphate in urine with 1.5 fold Mg concentration to PO4-P, the pH value was necessary to be more than 8.1 based on the model prediction